2009
DOI: 10.1083/jcb1865oia10
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-8 deficiency in epidermal keratinocytes triggers an inflammatory skin disease

Abstract: Expression of enzymatically inactive caspase-8, or deletion of caspase-8 from basal epidermal keratinocytes, triggers chronic skin inflammation in mice. Unlike similar inflammation resulting from arrest of nuclear factor B activation in the epidermal cells, the effect induced by caspase-8 deficiency did not depend on TNF, IL-1, dermal macrophage function, or expression of the toll-like receptor adapter proteins MyD88 or TRIF. Both interferon regulatory factor (IRF) 3 and TANK-binding kinase were constitutivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(69 citation statements)
references
References 15 publications
(19 reference statements)
1
68
0
Order By: Relevance
“…Previous studies have also reported an inflammasome-independent role for caspase-8 in inhibiting extensive inflammation in vivo. 72,73 Conditional deletion of caspase-8 in hepatocytes, augments Listeria infection in liver and chronic inflammation following hepatectomy. 73 Caspase-8 deficiency also protects against inflammation-related hepatocarcinogenesis, while inducing Although Ub-RIP1 can enhance the phosphorylation of IRF3, it is also cleaved by activated caspase-8.…”
Section: Caspases In Inflammation and Immunitymentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have also reported an inflammasome-independent role for caspase-8 in inhibiting extensive inflammation in vivo. 72,73 Conditional deletion of caspase-8 in hepatocytes, augments Listeria infection in liver and chronic inflammation following hepatectomy. 73 Caspase-8 deficiency also protects against inflammation-related hepatocarcinogenesis, while inducing Although Ub-RIP1 can enhance the phosphorylation of IRF3, it is also cleaved by activated caspase-8.…”
Section: Caspases In Inflammation and Immunitymentioning
confidence: 99%
“…74 In addition, conditional deletion of caspase-8 in epidermal keratinocytes, is associated with chronic skin inflammatory disease associated with constitutive IRF3 signaling. 72 Interestingly, this role for caspase-8 in suppressing inflammation is independent of signaling mediated through TNF, IL-1β or TLR receptors and independent of NFκβ signaling. Instead, caspase-8 regulates the activation of the IκK-related, TANK-binding kinase 1 (TBK1) and IRF3 to downregulate the inflammatory response.…”
Section: Caspases In Inflammation and Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, either Tak1 or caspase-8 deletion in the epidermis results in psoriasis-like skin inflammation resulting in animal mortality around postnatal days 5-8 (P5-8). 82,92 Inducible deletion of Tak1 or caspase-8 in the intestinal epithelium causes IBD-like intestinal inflammation, which is associated with loss of a specific cell type known as paneth cells. 55,93 Similarly, epidermal-and intestinal epithelium-specific deletion of Fadd, which abrogates caspase-8 activation, causes inflammatory skin disease and IBD-like ileitis.…”
Section: Pathology Of Tak1 Deficiency In a Variety Of Tissue In Mousementioning
confidence: 99%
“…Caspase-8-deficient epidermal cells show an increased inflammatory response towards transfected DNA, leading to chronic skin inflammation (Kovalenko et al 2009). …”
Section: Inhibition Of Inflammatory Responsesmentioning
confidence: 99%